Parental Allocations to Children: New Evidence on Bequest Differences among Siblings - Behrman, Jere R.; Rosenzweig, Mark R. (The Review of Economics and Statistics, 2004)
New survey-based data on siblings are used to assess potential roles of bequests in redistributing income among siblings as implied by prominent models. The data are not focused on the upper tail of the wealth distribution and include both own and sib reports on own and sib's bequests, enabling use of a measurement model. Results indicate that bequests are received by almost two-thirds of children, average bequests are significant fractions of annual earnings, and there are significant differences between sibs' schooling and earnings. However, there are not significant sib differences in bequests once measurement error is incorporated into the analysis.